Employee Retention- A Real Time Challenges In Indian IT Sector - Dhillon, Manju (IJRDO - Journal of Business Management, 2017)
Employee retention is most serious issue facing Indian IT sector due to shortage of skilled laboreconomic growth and employee turnover. It is not only important to have the best and the mosttalented employees but it is equally necessary to be able to retain them for long period of time. There are many factors which affects the retention of employee. Today global explosion inbusiness creates more opportunities and people are highly mobile not restricting to particular job. Human resources are the life-blood of any organization. Even though most of the organizations are now a days, found to be technology driven, yet human resources are required to run the technology. They are the most vital and dynamic resources of any organization. The purpose of his paper is to review the findings of research papers of various authors to derive the factors thataffect the employee retention and different employee retention strategies that are adopted by organizations to retain its employees.